Operational management model to increase the performance of an SME in the coffee shop sector: Puku Puku case - Gaviño Del Valle, Marco Aurelio (2024)
Innovation is a key factor for the competitiveness of SMEs, the service sector is characterized by recurring problems and fierce competition in a saturated market, causing these companies to reduce their profitability. This work presents an operational model to increase the performance of a coffee shop. For the design, a case study has been developed in “Puku Puku”, a coffee shop based in Lima, Peru. Applying the Huff Model, the company's competition was defined based on different relevant variables and, using benchmarking, a pricing strategy was implemented. For this purpose, a value was given to the distance from the premises to the consumer, price, location, customer satisfaction, among others; and the probability that a consumer would go to the different cafeterias in the studied area was obtained. Based on the results of this model, a report was made that provides a potential increase of 30% over the estimated income in the scenarios analyzed. The value of this research lies in the economic advantages that could be obtained by applying this model in a coffee shop business, with the possibility of being replicated in other areas.